Endocytic and recycling endosomes modulate cell shape changes and tissue behaviour during morphogenesis in Drosophila. - Ana Margarida Mateus; Nicole Gorfinkiel; Sabine Schamberg; Alfonso Martinez Arias (PLoS ONE)
During development tissue deformations are essential for the generation of organs and to provide the final form of an organism. These deformations rely on the coordination of individual cell behaviours which have their origin in the modulation of subcellular activities. Here we explore the role endocytosis and recycling on tissue deformations that occur during dorsal closure of the Drosophila embryo. During this process the AS contracts and the epidermis elongates in a coordinated fashion, leading to the closure of a discontinuity in the dorsal epidermis of the Drosophila embryo. We used dominant negative forms of Rab5 and Rab11 to monitor the impact on tissue morphogenesis of altering endocytosis and recycling at the level of single cells. We found different requirements for endocytosis (Rab5) and recycling (Rab11) in dorsal closure, furthermore we found that the two processes are differentially used in the two tissues. Endocytosis is required in the AS to remove membrane during apical constriction, but is not essential in the epidermis. Recycling is required in the AS at early stages and in the epidermis for cell elongation, suggesting a role in membrane addition during these processes. We propose that the modulation of the balance between endocytosis and recycling can regulate cellular morphology and tissue deformations during morphogenesis.